Conserving useful plants for a sustainable future: species coverage, spatial distribution, and conservation status within the Millennium Seed Bank collection - Udayangani Liu; Maraeva Gianella; Patricia Dávila Aranda; Mauricio Diazgranados; César Mateo Flores Ortíz; Rafael Lira-Saade; Silvia Bacci; Efisio Mattana; William Milliken; Olivia Mitrovits; Hugh W. Pritchard; Isela Rodríguez-Arévalo; et al. (Biodiversity and Conservation, 2023)
A substantially rich diversity of the world’s recorded useful plants (UPs) is captured within the Millennium Seed Bank collection hosted by the Royal Botanic Gardens, Kew, at Wakehurst, UK with 13,598 species (34%) belonging to 3696 genera and 325 families. This constitutes just over half of the total accessions and one third of the species and covers all 9 continents, 8 realms, 14 biomes, 34 biodiversity hotspots and 175 countries. The most common beneficial use category within the captured diversity is medicinal, then species with environmental, material, and human food value. About 86% of conserved UP species have a ‘Least Concern’ conservation status but 8% are identified as globally threatened. The advantages of mutual, continued, and long-term partnership (e.g., Mexico) are showcased when conserving plants important for local communities and addressing conservation challenges beyond seed banking. However, the geographic coverage suffers from a lack of partnerships with some parts of the world. Also, a low number of accessions contributed from many countries means that insufficient native range is yet to be captured for many species. This is particularly the case for restricted or narrow distribution species from families or genera with a high incidence of recalcitrant or short-lived seeds. Future planning must tailor better to cover the spatial distribution patterns for individual species, thereby improving the number of accessions and geographical coverage for those captured. Moreover, seed biology research should characterise desiccation tolerance and develop complementary, novel conservation methods, such as cryopreservation, to strengthen conservation options for UP species.

Development of twenty-one polymorphic microsatellite markers for the fungus-growing ant, Mycocepurus goeldii (Formicidae: Attini), using Illumina paired-end genomic sequencing - Christian Rabeling; Cara N. Love; Stacey L. Lance; Kenneth L. Jones; Naomi E. Pierce; Mauricio Bacci (Conservation Genetics Resources, 2014)

Yeasts associated with nests of the leaf-cutting ant Atta sexdens rubropilosa Forel, 1908 - Solange Cristina Carreiro; Fernando Carlos Pagnocca; Odair Correa Bueno; Mauricio Bacci Júnior; Maria José Aparecida Hebling; Osvaldo Aulino da Silva (Antonie van Leeuwenhoek, 1997)